The Acoustic Features of Inhalation can be Used to Quantify Aerosol Delivery from a Diskus (TM) Dry Powder Inhaler - REILLY, RICHARD (My University, 2014)
Purpose Some patients are unable to generate the peak inspiratory flow rate (PIFR) necessary to de-agglomerate drug particles from dry powder inhalers (DPIs). In this study we tested the hypothesis that the acoustic parameters of an inhalation are related to the PIFR and hence reflect drug delivery. Methods A sensitivity analysis of the relationship of the acoustics of inhalation to simultaneously recorded airflow, in a cohort of volunteers (n = 92) was performed. The Next Generation Impactor (NGI) was used to assess in vitro drug delivery from salmeterol/fluticasone and salbutamol Diskus (TM) DPIs. Fine particle fraction, FPF, (<5 mu m) was measured at 30-90 l/min for 2-6 s and correlated with acoustically determined flow rate (IFRc). In pharmacokinetic studies using a salbutamol (200 mu g) Diskus (TM), volunteers inhaled either at maximal or minimal effort on separate days. Results PIFRc was correlated with spirometrically determined values (R-2=0.88). In in vitro studies, FPF increased as both flow rate and inhalation duration increased for the salmeterol/fluticasone Diskus (TM) (Adjusted R-2=0.95) and was proportional to flow rate only for the salbutamol Diskus T (Adjusted R-2=0.71). In pharmacokinetic studies, blood salbutamol levels measured at 20 min were significantly lower when PIFRc was less than 60 l/min, p<0.0001. Conclusion Acoustically-determined PIFR is a suitable method for estimating drug delivery and for monitoring inhalation technique over time.
PUBLISHED
Keywords: Inhalation